1991
DOI: 10.1042/bj2770097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mg2+ on the binding of oxytocin to sheep myometrial cells

Abstract: Binding isotherms of oxytocin to sheep myometrial cells in a short-term cell culture were investigated in the presence of Mg2+ in the concentration range 0-10 mM. The occurrence of at least three binding sites had been demonstrated earlier. Mg2+ influences individual sites and individual features of the binding isotherm differently. Dissociation constants (Kd) of the high- and medium-affinity sites attain a minimum of 6.8 x 10(-10) and 4.2 x 10(-8) mol/l respectively at 2.75 mM-Mg2+. The two sites display the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Although there have been a number of studies on the binding of oxytocin to its receptor in rat (Soloff ef al., 1979), sheep (PliSka andKohlhauf Albertin, 1991), cow (Jenner et al, 1991), and human uterus (Fuchs ef al., 1984), no detailed studies have been carried out in terms of association and dissociation kinetics. The present kinetic studies revealed that the affinity of longitudinal muscle membrane receptors for oxytocin increased through an increase in the association rate and a decrease in the dissociation rate with the progress of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been a number of studies on the binding of oxytocin to its receptor in rat (Soloff ef al., 1979), sheep (PliSka andKohlhauf Albertin, 1991), cow (Jenner et al, 1991), and human uterus (Fuchs ef al., 1984), no detailed studies have been carried out in terms of association and dissociation kinetics. The present kinetic studies revealed that the affinity of longitudinal muscle membrane receptors for oxytocin increased through an increase in the association rate and a decrease in the dissociation rate with the progress of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of cholesterol to the culture medium reversed a fraction of OT-receptors to the high-affinity state (K d around 1nM) [217]. The effects of divalent cations on the binding affinity of OT-R agonists are very similar to those produced by cholesterol [218]. Peptides with relatively low activity, such as 7-glycine OT became significantly more potent on uterine, but not mammary gland, receptors when the Mn 2+ concentration in the buffer bathing the uterine smooth muscle was increased [219].…”
Section: Target Structure Function Localisationmentioning
confidence: 88%
“…The total number of computational cycles is (n-4)(n-5)/2, (n-3)(n-4)/2 and (n-2)(n-3)/2 for the three options [31]. The use of the full version, moreover, is occasionally associated with certain numeric difficulties.…”
Section: The Binding Isotherm Turns Then Into An Integral Formmentioning
confidence: 99%